Global Challenges and Local Responses: Trade Unions in the Korean and Malaysian Auto Industries - Peter Wad (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2005)
The paper aims to address the question whether the dynamic of autoworker unionism in South Korea and Malaysia was conditioned by, and eventually also influenced the globalization processes in the local auto industry? The conclusion is a contextualized "yes", and the core argument is the following: The financial crisis in 1997 was the dramatic peak of financial globalization in East Asia in the 1990s, and it did accelerate the existing trend in Korea towards centralized unionism in the auto industry, while it suspended the trend in the Malaysian auto industry towards decentralized unionism. Although the Korean and Malaysian unions were affected by the financial crisis from different structural and strategic positions, and were exposed to different national policies and corporate strategies of crisis management, the Korean unions and Malaysian unions generally followed, respectively, a more radical and militant and a more pragmatic and moderate strategy. In the global-local perspective we face two paradoxes. The first paradox is that in spite of the difference in union ideology, the outcome in terms of industrial relations (IR) institutions was rather similar in the sense that the auto industry contained a mixture of industrial and enterprise unions and formal or informal federations of these unions, and that collective bargaining was by and large undertaken bilaterally at the enterprise level. This situation was generated by a dynamic, which took the Malaysian system down from a centralized IR system within the low technology assembly industry (the globally subordinated local OEMs) to a rather decentralized IR system within the SOE-MNC controlled industry. The Korean system became more centralized through the confrontations between radical enterprise unions and authoritarian employers and authorities within an auto industry, which over time become much more indigenized, technologically advanced, export-oriented and diversified into multiple auto manufacturers and an under-wood of component suppliers. Yet, in both auto industries the large enterprise unions resisted organizational centralization, which could impede their autonomy. Due to the strength of unions of the market leading firms a breakthrough did happen neither in Korea nor in Malaysia, although the Koreans were a step ahead of the Malaysians having established a federation of metalworkers unions, including the important autoworkers unions. The second paradox is that the radicalism of the Korean autoworker unions was maintained during 1990s globalization of the auto industry, while radicalism was abandoned by the Malaysian autoworker unions in favor of union pragmatism, when the indigenization of the Malaysian auto industry unfolded since the early 1980s and a local auto supplier industry had been formed. This cross-country difference is partly explained by the different position held by the Korean and Malaysian auto companies in the global and local auto value chain. The radicalism and effectiveness of Korean autoworker unions sustained the development of dynamic efficiency among Korean auto manufacturing firms. In the same way, the intra-industry differences in wages and working conditions among auto manufacturing firms and components supplier firms were also related to the stratification of the domestic auto value chain, and this uneven distribution of benefits created obstacles of centralized unionization and collective bargaining. The centralized IR system in Malaysia evolved in an auto industry composed primarily of firms assembling imported CKD kits of components. The inequality of employment conditions between auto manufacturers and component suppliers was a driver of the strategy of centralized unionism and collective bargaining in Korea, while the inequality was not perceived as that significant by the Malaysian industrial union, since they had been dealing with these problems by the early 1990s. Keywords: Globalisation, trade unions, automobile industry, global value chain theory, East Asia, Malaysia, South Korea.
hdl:10398/7410
Keywords: 330